Digital Storytelling Reinvents the News: The Rise of Data Journalism and Its Impact on Libraries. - Herther, Nancy K. (Online Searcher)
In an increasingly digital world, information can be expressed in startling and incredible ways. In December 2012, The New York Times published "Snow Fall: The Avalanche at Tunnel Creek," a six-part story that included interactive graphics, animated simulations, and aerial video. The series resulted in 2013 Pulitzer (pulitzer.org/winners/john-branch) and Peabody (peabodyawards.com/awardprofile/snow-fall-the-avalanche-at-tunnelcreek) awards and became an important landmark in the history of journalism. It also appeared in print in the Dec. 21, 2012, issue of the newspaper, obviously without the multimedia components.